Online coach development and certification programs in sports: Are they possible? - Papageorgiou, K. G. (Central European Journal of Sport Sciences and Medicine, 2020)
Anticipating the inevitable shift of coach education and Coach Certification Programs (CCP) to distance-learning platforms in the imminent future, I have attempted to identify obstacles that we are likely to face. After explaining the rationale and the potential benefits of such courses, I have identified technique as the most difficult component to both teach and evaluate. A specific viewpoint regarding technique is briefly discussed and several related guidelines are provided to assist in both teaching (coach education) and evaluating technique (CCP) within the context of distance education.